Living with tuberculosis: a qualitative study of patients' experiences with disease and treatment - Juliet Addo; Dave Pearce; Marilyn Metcalf; Courtney Lundquist; Gillian Thomas; David Barros-Aguirre; Gavin C. K. W. Koh; Mike Strange (BMC, 2022)
Abstract Background Although tuberculosis (TB) is a curable disease, treatment is complex and prolonged, requiring considerable commitment from patients. This study aimed to understand the common perspectives of TB patients across Brazil, Russia, India, China, and South Africa throughout their disease journey, including the emotional, psychological, and practical challenges that patients and their families face. Methods This qualitative market research study was conducted between July 2020 and February 2021. Eight TB patients from each country (n = 40) completed health questionnaires, video/telephone interviews, and diaries regarding their experiences of TB. Additionally, 52 household members were interviewed. Patients at different stages of their TB treatment journey, from a range of socioeconomic groups, with or without TB risk factors were sought. Anonymized data underwent triangulation and thematic analysis by iterative coding of statements. Results The sample included 23 men and 17 women aged 13-60 years old, with risk factors for TB reported by 23/40 patients. Although patients were from different countries and cultural backgrounds, experiencing diverse health system contexts, five themes emerged as common across the sample. 1) Economic hardship from loss of income and medical/travel expenses. 2) Widespread stigma, delaying presentation and deeply affecting patients' emotional wellbeing. 3) TB and HIV co-infection was particularly challenging, but increased TB awareness and accelerated diagnosis. 4) Disruption to family life strained relationships and increased patients' feelings of isolation and loneliness. 5) The COVID-19 pandemic made it easier for TB patients to keep their condition private, but disrupted access to services. Conclusions Despite disparate cultural, socio-economic, and systemic contexts across countries, TB patients experience common challenges. A robust examination of the needs of individual patients and their families is required to improve the patient experience, encourage adherence, and promote cure, given the limitations of current treatment.